Transcriptome analysis of the aged SAMP8 mouse model of Alzheimer’s disease reveals novel molecular targets of formononetin protection - Liu, Bo; Cui, Di; Liu, Jie; Shi, Jing-Shan (Frontiers in Pharmacology, 2024)
Background: Senescence accelerated mouse prone 8 (SAMP8) and age-matched SAMR1 mice are used to study the pathogenesis and therapeutics of Alzheimer's disease (AD), however, the molecular mechanisms are not completely understood. Objective: This study aimed to examine the effects of 5-month administration of Formononetin in SAMP8 mice and used RNA-Seq to explore the molecular targets. Methods: SAMP8 mice were orally given Formononetin (0, 8 and 16 mg/kg) from 4 months of age, and age-matched SAMR1 mice were used as controls.Behavioral tests were performed in 9-month-old mice, followed by histopathology. Total RNA from hippocampus was isolated and subjected to RNA-Seq, RT-qPCR, and bioinformatics analysis.: The 9-month-old SAMP8 mice exhibited cognition deficits evidenced by Novel object recognition, Open field test, Elevated plus maze and Passive avoidance. Nissl bodies in the cortex and hippocampus were decreased. Formononetin treatments ameliorated behavioral deficits and improved morphological changes, which were evidenced by Nissl and H&E staining. RNA-Seq revealed distinct gene expression pattern between SAMP8 and SAMR1 mice. Differentially expressed genes in SAMP8 mice were attenuated or normalized by Formononetin. Ingenuity pathway analysis of Canonical pathway and Upstream regulators revealed increases in proinflammatory factors, immune dysfunction and decreases in NRF2 and SIRT-1 signaling pathways, leading to neuroinflammation. Formononetin treatment attenuated or reversed these molecular changes. The transcriptome of SAMP8 mice was correlated with transcriptome profiles of other AD mouse models in GEO database. Conclusion: Neuroinflammation and decreased antioxidative and SIRT-1 signaling contributed to cognitive deficit in aged SAMP8 mice, which are potential therapeutic targets of Formononetin in combination with other therapies.